2018
DOI: 10.1002/brb3.1099
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐based meta‐analysis of gray and white matter volume abnormalities in spinocerebellar ataxia type 2

Abstract: ObjectiveTo identify the consistent findings from the whole‐brain voxel‐based morphometry (VBM) studies on spinocerebellar ataxia type 2 (SCA2).MethodsThe whole‐brain VBM studies comparing SCA2 patients and healthy controls (HCs) were systematically searched in PubMed, Embase databases from January 2000 to June 2017. The coordinates with significant differences in gray matter (GM) and white matter (WM) between SCA2 patients and HCs were extracted separately from each cluster. A meta‐analysis was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Atrophy of the right temporo-occipital cortex (parahippocampal, fusiform and lingual gyri) was observed in a meta-analysis of the VBM studies [14] (Figure 2). Striata and thalami have normal volumes [12,14].…”
Section: Structural and Microstructural Mr Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Atrophy of the right temporo-occipital cortex (parahippocampal, fusiform and lingual gyri) was observed in a meta-analysis of the VBM studies [14] (Figure 2). Striata and thalami have normal volumes [12,14].…”
Section: Structural and Microstructural Mr Imagingmentioning
confidence: 99%
“…Differently from multiple system atrophy, the T2 signal in the striata is normal [9,11] (Figure 1). Morphometry performed on T1-weighted images using volumetry of regions of interest or whole-brain analytical software, including voxel-based morphometry (VBM) or tensor-based morphometry, allows a quantitative assessment of the selective brainstem and cerebellar atrophy in SCA2 [12][13][14] (Figure 2) which is already present in pre-symptomatic gene carriers [15,16] ( Figure 3). Atrophy of the right temporo-occipital cortex (parahippocampal, fusiform and lingual gyri) was observed in a meta-analysis of the VBM studies [14] (Figure 2).…”
Section: Structural and Microstructural Mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The lobule X is also known as flocculonodular lobe and it plays an important role in regulating and orienting the eye movement through vestibulo-ocular reflex (Stoodley and Schmahmann, 2009 ; Stoodley et al, 2012 ). It also affects the body equilibrium during stance and gait along with lobule IX (Han et al, 2018 ). Thus, any change in the volume of lobule X may directly affect movement of eyes which is usually seen in ataxias (nystagmus).…”
Section: Discussionmentioning
confidence: 99%
“…Recent fractal analysis on the index of the structural complexity of the cortical gray matter and white matter demonstrated the reduction of the structural complexity of the cerebellum and cerebral cortex in SCA2 patients in vivo [71]. The recent whole-brain voxel-based morphometry (VBM) in vivo studies on SCA2 showed that the gray matter volume reductions in SCA2 patients were mainly observed in the cerebellum and the part of the cerebral cortex in the supratentorial regions responsible for the regulation of cognitive functions and emotions, whereas significant white matter volume reductions widely existed in the cerebellum along with its afferent pathways and pyramidal system [72]. Another recent VBM study has shown the significant gray matter loss in the bilateral regions of the anterior cerebellar hemisphere (I-V), the posterior lobe (VI-IX), and the posterior vermis (VI-IX).…”
Section: Cerebellar Atrophy In Sca2mentioning
confidence: 99%